Capability, compatibility, and usability evaluation of hardware-in-the-loop platforms for DC-DC converter - Maxwell, S.; Islam, Syed; Hossain, M.; Park, S. (2016)
© 2016 IEEE. This paper evaluates the capability, compatibility, and usability of Hardware-in-the-Loop platforms for DC-DC converter. This was accomplished by interfacing the platforms with a physical power stage as well as a controller. The employed platforms are Hi-Rel Power-pole board, Texas Instruments Digital Controller, RTDS, OPAL-RT, dSPACE, and Typhoon. Two sets of experimentation were performed: the power stage represented by the Power-pole board, RTDS, OPAL-RT, dSPACE, and Typhoon and the controller replaced by TI DSC, RTDS, OPAL-RT, dSPACE, and Typhoon. Three points of evaluation for a testing platform that are of interest to industrial researchers as well as academia are capability (speed or modeling capacity), compatibility (ease of porting models from other platforms), and usability (ease of use of software and hardware). This paper provides an introductory resource for research and education by providing results of a simple buck converter example.